2019
DOI: 10.1111/btp.12715
|View full text |Cite
|
Sign up to set email alerts
|

Climate severity and land‐cover transformation determine plant community attributes in Colombian dry forests

Abstract: Tropical dry forests (TDF) are known to be resource‐limited due to a marked seasonality in precipitation. However, TDF are also shaped by factors such as solar radiation, wind speed, soil fertility, and land‐cover transformation. Together, these factors may determine different gradients of environmental harshness that are likely to drive changes in plant community attributes. Here, we evaluated the effects of environmental harshness on plant community diversity and structure of Colombian TDF, based on floristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 92 publications
2
13
0
Order By: Relevance
“…Some studies have shown that precipitation and soil properties affect current patterns of species diversity in the tropical dry forest (e.g., [35,70,71]); in this sense, our results also indicate that precipitation seasonality is the most important variable for explaining species…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some studies have shown that precipitation and soil properties affect current patterns of species diversity in the tropical dry forest (e.g., [35,70,71]); in this sense, our results also indicate that precipitation seasonality is the most important variable for explaining species…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown that precipitation and soil properties affect current patterns of species diversity in the tropical dry forest (e.g., [ 35 , 70 , 71 ]); in this sense, our results also indicate that precipitation seasonality is the most important variable for explaining species richness in the SDTF. Therefore, the highest Asteraceae richness values concentrate in relatively high and stable humidity conditions, such as those found in the Upper Balsas district.…”
Section: Discussionsupporting
confidence: 79%
“…Tropical dry forest is an ideal model for understanding how tree species cope with drought. First, it presents a strong dry season where soil water deficit limits tree species' growth and establishment (Murphy & Lugo, 1986;González-M et al, 2019). Second, strategies to cope with water deficit have been wellstudied in adult individuals, but it is unclear whether these strategies are fully developed from the seedling ontogenetic stage.…”
mentioning
confidence: 99%
“…Second, strategies to cope with water deficit have been wellstudied in adult individuals, but it is unclear whether these strategies are fully developed from the seedling ontogenetic stage. And third, high fragmentation rates in this ecosystem can amplify the climatic severity due to the edge effects with effects on its structure and diversity (González-M et al, 2019). Understanding the functional mechanisms that determine seedling establishment will strengthen our ability to predict and understand these forests' future under climate change scenarios in which greater seasonality and reductions in rainfall are expected (Dai, 2013;Feng et al, 2013).…”
mentioning
confidence: 99%
“…This information has shown that species diversity, forest basal area, and canopy height decrease as drought and landscape transformation increase (González‐M. et al., 2019). Data have also provided insights on patterns of TDF tree species' abundance and spatial distribution, showing that almost half of the species recorded in permanent plots are extremely rare and as much as 80% exhibit a restricted distribution (Norden et al, 2019).…”
Section: Comprehensive Management Of Tdf Built Upon Permanent Plotsmentioning
confidence: 99%